Lebanese Cannabis sativa L. extract protects from cisplatin-induced nephrotoxicity in mice by inhibiting podocytes apoptosis - Alia Khalil; Sahar Al Toufaily; Wassim Shebaby; Marissa El Hage; Dima Mroue; Wissam Faour; Mohamad Mroueh (Journal of Cannabis Research)
Abstract Background Cisplatin is an anti-cancer drug used to treat a plethora of solid tumors. However, it is associated with dose dependent nephrotoxicity limiting its use as anticancer agent. Objective The current study aimed to investigate the nephroprotective effect of native Lebanese Cannabis sativa in both in vitro and in vivo mice model of cisplatin-induced nephrotoxicity. Methods Podocytes cell viability was assessed using MTS assay with cisplatin (30µM) in presence or absence of Cannabis oil extract (COE) at 0.5, 1 and 2µg/ml for 24h. Acute renal injury was established in adult female C57BL/6 mice with 20mg/kg, i.p. single dose cisplatin. Mice were divided into control group (vehicle), COE group, cisplatin group and cisplatin plus COE (2.5, 5 and 20mg/kg, i.p.). Animal body weight, serum creatinine, blood urea nitrogen (BUN), and proteinuria were measured. Results Cell viability assay and western blot analysis revealed that COE prevented apoptosis induced by cisplatin in cultured immortalized rat podocytes. In addition, in vitro scratch assay demonstrated the ability of COE to promote and restore the migratory capacity of podocytes in cisplatin-treated cells. Interestingly, COE treatment improved urinary and serum parameters characterized by a significant decrease in serum creatinine, urea, and proteinuria at various COE doses. Western blot analysis showed that COE inhibited COX-2 protein induction as well as apoptosis marker production (Bax/Bcl2 ratio) in cisplatin-treated mice when compared to mice treated with cisplatin alone. Conclusion Collectively, the aforementioned findings indicate that COE could be a promising approach to protect against cisplatin-induced nephrotoxicity.